2013
DOI: 10.1111/tri.12069
|View full text |Cite
|
Sign up to set email alerts
|

Living donor age and kidney transplant outcomes: an assessment of risk across the age continuum

Abstract: SummaryDetailed data on living donor age, and its interplay with recipient age, in predicting allograft and recipient outcomes are wanting. We used the Scientific Registry of Transplant Recipients (2000Recipients ( -2009, n = 49 589) to assess the effect of living donor age on delayed graft function (DGF), total graft failure, death-censored graft failure, death with graft function, and graft failure with death as a competing risk using logistic and Cox proportional hazards models. Potential nonlinear associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
2
17
0
4
Order By: Relevance
“…6 Previous studies also indicate increased graft failure among recipients as donor age increases [7][8][9] ; however, these studies have been conflicted and used varying definitions of older living donors. Although long-term studies have not demonstrated an additional mortality risk for living kidney donors, 5 they have demonstrated an increased risk of end-stage renal disease, with the highest rates among older donors.…”
mentioning
confidence: 99%
“…6 Previous studies also indicate increased graft failure among recipients as donor age increases [7][8][9] ; however, these studies have been conflicted and used varying definitions of older living donors. Although long-term studies have not demonstrated an additional mortality risk for living kidney donors, 5 they have demonstrated an increased risk of end-stage renal disease, with the highest rates among older donors.…”
mentioning
confidence: 99%
“…According to the 2006 United States Renal Data System report, the risk of DGF in transplants from living donors above the age of 65 years is double that of transplants from younger donors [22]. Another report, a retrospective cohort study of 49,589 recipients between 2000 and 2009 in the United States, showed that for every 10-year increase in living donor age, the odds of DGF increased by 15% [23]. These observations can be partly explained by the impaired ability for repair in kidneys from elderly donors [24].…”
Section: Effects Of Aging On Kidney Functionmentioning
confidence: 99%
“…This study however, had a relatively small number of living donors >60 years and did not account for death as a competing risk. A more recent retrospective cohort study [23] demonstrated significant differences in overall survival, and death censored survival and death with graft function in recipients stratified according to living donor age categories. They reported a 53% increase in the hazard for total graft failure in recipients of kidneys from donors >60 years compared to donors between 18 and 29.9 years.…”
Section: Outcome Of Transplantation From Elderly Living Donorsmentioning
confidence: 99%
“…1,2 LRKT is associated with longer graft and patient survival as compared to deceased donor kidney transplantation. 3,4 The improved outcomes associated with LRKT are best explained by a reduction in ischemic injury, shorter waiting time on dialysis, and the transplantation of ''healthier'' kidney tissue when compared to deceased donor kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%